The importance of examining early maladaptive schemas in the diagnosis and treatment of obsessive-compulsive disorder - Csigó, Katalin; Münnich, Ákos; Molnár, Judit (Frontiers in Psychiatry, 2024)
Obsessive-compulsive disorder is the fourth most common psychiatric disease. Partly the high rate of subclinical forms of OCD and partly the high rate of non-responders forms of OCD new diagnostic and psychotherapeutic methods developments are essential in our clinical practice. The aim of the study was twofolded: to identify the early maladaptive schemas characteristic of obsessive-compulsive disorder in a Hungarian sample and, to examine the presence and severity of comorbid anxiety and depressive symptoms in the light of early maladaptive schemas. We identified five early maladaptive schemas with a direct effect on the manifestation of obsessive-compulsive symptoms and the results highlight that OCD is only one and not the most serious consequence of personality damage, indicated by early maladaptive schemas. Our results strengthen the new dimensional view of OCD.